Fosfomycin vs Ertapenem for Outpatient Treatment of Complicated Urinary Tract Infections: A Multicenter, Retrospective Cohort Study. (23rd December 2021) - Wald-Dickler, Noah; Lee, Todd C; Tangpraphaphorn, Soodtida; Butler-Wu, Susan M; Wang, Nina; Degener, Tyler; Kan, Carolyn; Phillips, Matthew C; Cho, Edward; Canamar, Catherine; Holtom, Paul; Spellberg, Brad
Abstract: Background: We sought to determine the comparative efficacy of fosfomycin vs ertapenem for outpatient treatment of complicated urinary tract infections (cUTIs). Methods: We conducted a multicenter, retrospective cohort study involving patients with cUTI treated with outpatient oral fosfomycin vs intravenous ertapenem at 3 public hospitals in Los Angeles County between January 2018 and September 2020. The primary outcome was resolution of clinical symptoms 30 days after diagnosis. Results: We identified 322 patients with cUTI treated with fosfomycin (n = 110) or ertapenem (n = 212) meeting study criteria. The study arms had similar demographics, although patients treated with ertapenem more frequently had pyelonephritis or bacteremia while fosfomycin-treated patients had more retained catheters, nephrolithiasis, or urinary obstruction. Most infections were due to extended-spectrum β-lactamase–producing E. coli and Klebsiella pneumoniae, 80%–90% of which were resistant to other oral options. Adjusted odds ratios for clinical success at 30 days, clinical success at last follow-up, and relapse were 1.21 (95% CI, 0.68–2.16), 0.84 (95% CI, 0.46–1.52), and 0.94 (95% CI, 0.52–1.70) for fosfomycin vs ertapenem, respectively. Patients treated with fosfomycin had significant reductions in length of hospital stay and length of antimicrobial therapy and fewer adverse events (1 vs 10). Fosfomycin outcomes were similar irrespective of duration of lead-in intravenous (IV) therapy or fosfomycin dosing interval (daily, every other day, every third day). Conclusions: These results would support the conduct of a randomized controlled trial to verify efficacy. In the meantime, they suggest that fosfomycin may be a reasonable stepdown from IV antibiotics for cUTI.